Pharmacological and Genetic Reversal of Age-Dependent Cognitive Deficits Attributable to Decreased presenilin Function - McBride, Sean M. J. (Society for Neuroscience, 2010)
Alzheimer's disease (AD) is the leading cause of cognitive loss and neurodegeneration in the developed world. Although its genetic and environmental causes are not generally known, familial forms of the disease (FAD) are attributable to mutations in a single copy of the Presenilin (PS) and amyloid precursor protein genes. The dominant inheritance pattern of FAD indicates that it may be attributable to gain or change of function mutations. Studies of FAD-linked forms of presenilin (psn) in model organisms, however, indicate that they are loss of function, leading to the possibility that a reduction in PS activity might contribute to FAD and that proper psn levels are important for maintaining normal cognition throughout life. To explore this issue further, we have tested the effect of reducing psn activity during aging in Drosophila melanogaster males. We have found that flies in which the dosage of psn function is reduced by 50% display age-onset impairments in learning and memory. Treatment with metabotropic glutamate receptor (mGluR) antagonists or lithium during the aging process prevented the onset of these deficits, and treatment of aged flies reversed the age-dependent deficits. Genetic reduction of Drosophila metabotropic glutamate receptor (DmGluRA), the inositol trisphosphate receptor (InsP(3)R), or inositol polyphosphate 1-phosphatase also prevented these age-onset cognitive deficits. These findings suggest that reduced psn activity may contribute to the age-onset cognitive loss observed with FAD. They also indicate that enhanced mGluR signaling and calcium release regulated by InsP(3)R as underlying causes of the age-dependent cognitive phenotypes observed when psn activity is reduced.